Semiotic Niche Construction in Musical Meaning - Atã, Pedro; Queiroz, João (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2017)
According to Peirce’s pragmatic semiotics, meaning (semiosis) is not an infused concept, but a power to engender interpretants. Semiosis is a triadic, context-sensitive (situated), interpreter-dependent (dialogic), materially extended (embodied and distributed) dynamic process. Although meaning is context-sensitive and materially extended, its locus is not well-captured by the notion of an environment. Inspired by biological concepts, we suggest the locus of meaning to be a niche. Here, we develop a semiotic account of musical meaning that emphasizes the location of musical signs in semiotic niches.